PENGELOLAAN DOKUMEN PRIBADI BERBASIS DIGITAL PADA MAHASISWA - Shely Alfia Mufida; Andini Nisrina Najiyah; Rifa Arifatuz Zahroh; Anastasya Gale Nango; Adinda Putri Dwi Lestari; Najwa Nur Azizah (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2026)
This study aims to examine the behavior of undergraduate (S-1) and applied undergraduate (D-IV) students at Airlangga University in managing personal digital documents using the Personal Information Management (PIM) framework. A descriptive quantitative approach was used to collect data from 100 valid respondents, which was analysed using percentage and frequency distribution techniques. This study shows that the acquisition of digital documents via messaging apps, collaboration platforms and internet searches has become the main channel. During the management stage, most respondents used laptops, smartphones and cloud storage to organise documents hierarchically by activity and title. Although the process of retrieval and evaluation has been done systematically and periodically by systematic search and review of files, the practice of organisation and long-term maintenance still requires standardisation so that the management of digital student documents runs more consistently.